Effect of Oyster mushroom in Paracetamol Induced Toxicity of Liver in Wistar albino Rats - Sumy, Afroza Khanam; Jahan, Nasim; Sultana, Nayma; Sikder, Abdul Mannan (Journal of Enam Medical College, 2014)
Backgroud: Liver is an important metabolic organ. It has wide range of functions including detoxification, storage of glycogen, vitamins A, D and B12, production of several coagulation factors, growth factors such as insulin-like growth factor-1 (IGF-1), angiotensinogen, and biochemicals necessary for digestion (bile). Its damage occurs due to its multidimensional functions, various xenobiotics and oxidative stress leading to distortion of all of its functions. Oyster mushroom which is excellently edible and nutritious has got free radical scavenging activity, and so may be considered as a hepatoprotective agent. Objective: To observe the hepatoprotective effect of Oyster mushroom (Pleurotus florida) against paracetamol induced liver damage in Wistar albino rats. Materials and Methods: This experimental study was carried out in the Department of Physiology, Sir Salimullah Medical College (SSMC), Dhaka from 1st July 2009 to 30th June 2010. Thirty four Wistar albino rats, aged 90 to 120 days, weighing between 150 to 210 grams were used for the study. After acclimatization for 14 days, they were divided into two groups control group (Group A) and experimental group (Group B, mushroom-pretreated and paracetamol-treated group). Control group was again subdivided into Group A1 (baseline control group) and Group A2 (paracetamol-treated control group). Animals of all groups received basal diet for 30 consecutive days. In addition, Group A1 rats received propylene glycol (2 mL/kg body weight orally) only on 30th day, Group A2 rats received single dose of paracetamol suspension (750 mg/kg body weight orally) only on 30th day and Group B rats received mushroom extract (200 mg/kg body weight orally) for 30 consecutive days and paracetamol suspension (750 mg/kg body weight orally) only on 30th day. All the animals were sacrificed on 31st day. Then liver specimens were collected. Histology of liver was done by using standard laboratory procedure. Statistical analysis was done by one way ANOVA test by using SPSS version 15.0. Result: In this study, histological examination of liver reveals abnormal histological findings in 100% of rats in paracetamol-treated group (Group A2), almost normal structure in 80% of rats and mild histological changes in 20% rats in mushroom-pretreated and paracetamol-treated group (Group B). Conclusion: The present study reveals the hepatoprotective effect of Oyster mushroom (Pleurotus florida) against paracetamol induced liver damage in Wistar albino rats. DOI: http://dx.doi.org/10.3329/jemc.v4i3.20945 J Enam Med Col 2014; 4(3): 161-167